Covid-19 Outbreak In Italy: Are We Ready for the Psychosocial and the Economic Crisis? Baseline Findings From the PsyCovid Study - Cerami, Chiara; Santi, Gaia C.; Galandra, Caterina; Dodich, Alessandra; Cappa, Stefano F.; Vecchi, Tomaso; Crespi, Chiara (Frontiers in Psychiatry, 2020)
The Covid-19 pandemic is burning all over the world. National healthcare systems are facing the contagion with incredible strength, but concern regarding the psychosocial and economic effects is growing quickly. The PsyCovid Study assessed the influence of psychosocial variables on individual differences from the perceived impact of the Covid-19 outbreak on the issues of health and economy in the Italian population. Italian volunteers from different regions completed an online anonymous survey. The main outcomes were the perceived impact of the Covid-19 outbreak on health and the economy. A two-way MANOVA evaluated differences in the main outcomes, with geographical area (northern, central, and southern regions) and professional status (healthcare workers or not) as factors. We then tested the relationship linking psychosocial variables (i.e. perceived distress and social isolation, empathy, and coping style) to the main outcomes through two different mediation models. 1163 responders completed the survey (835 females; mean age: 42 ± 13.5 y.o.; age range: 18-81 y.o.) between March 14 and 21, 2020. Healthcare workers and people living in northern Italy reported a significantly worse outbreak impact on health, but not on the economy. In the whole sample, distress and loneliness were key variables influencing the perceived impact of the Covid-19 outbreak on health, while empathy and coping style affected the perceived impact on the economy. The Covid-19 pandemic is a worldwide emergency in terms of psychological, social, and economic consequences. Our data suggests that in the Italian population, actual differences in individual perception of the Covid-19 outbreak severity for health are dramatically modulated by psychosocial frailty (i.e., distress and loneliness). At the same time, problem-oriented coping strategies and enhanced empathic abilities increase people's awareness of the severity of the impact of the Covid-19 emergency on economics. There is an immediate need for consensus guidelines and healthcare policies to support interventions aimed to manage psychosocial distress and increase population resilience towards the imminent crisis.